Evaluation of association between periodontitis in pregnant women and preeclampsia - Pratibha Jha; Sumedha Singh; Ratan Kumar Dutta (Wolters Kluwer -Medknow Publications, 2024)
Background and Objective: Preeclampsia is a maternal disease encountered during the second half of pregnancy. Many risk factors have been implicated in its pathogenesis. Periodontitis may burden pregnant patients systemically with cytokines and endotoxin at the maternal fetal interface leading to endothelium dysfunction. Hence, our objective was to check the association between periodontitis and preeclampsia. Materials and Methods: This observational study was conducted in the outpatient department (OPD) of community health center from March 15, 2022, to December 14, 2022, on 100 patients. Inclusion Criteria Pregnant women of age group >18 years with informed consent with gestational age between 26 and 36 weeks with Singleton pregnancy. Women with a history of smoking, alcohol and periodontal treatment, multiple pregnancy, and consumption of antibiotics (3 months before study inclusion) were excluded. All eligible candidates in the antenatal clinic in OPD of obstetrics and gynecology were screened by history, obstetrical examination, routine antenatal tests, including urine routine and blood pressure measurement. Subjects were evaluated as per the designed protocol. Fifty preeclamptics were taken as case and 50 non preeclamptic were taken as control. Oral examination was conducted on the patients at the inclusion in the study and followed till delivery. Blood pressure and urine albumin were checked at each visit. Details noted on delivery and outcomes were observed. Results: The risk of preeclampsia in women having periodontitis showed an odds ratio of 3.436 (95% confidence interval: 1.460-8.065; P = 0.006). Conclusion: As the etiology of both events is multifactorial preeclampsia and periodontitis relationship needs wise attention.